Glycosylation as regulator of human B-cell leukaemias in bone marrow - Heisterkamp, Nora (Frontiers in Hematology, 2023)
Leukemic B-cells are lodged in the bone marrow [BM], a complex organ composed of many cell types and extracellular matrix. Determining how the reciprocal interactions between these components are regulated is critical to our understanding of the factors that allow leukemia cells to survive, multiply and withstand treatment. All cells in the bone marrow are surrounded by a glycocalyx, a glycan-rich layer of high complexity, which regulates such cell-cell and cellmatrix interactions. However, the structure and function of the glycan components of the biomolecules that constitute this layer have not been explored in much detail. Gaps are difficult to fill due to technical limitations as well as the fact that the composition of the BM in health, disease and aging is not static. This also applies to B-lineage malignancies that develop or persist in BM such as B-cell precursor acute lymphoblastic leukemia and Multiple Myeloma, and the effects of their treatment. In contrast, the proteomes and transcriptomes of different human bone marrow cells have been studied more extensively. A combination of technologies now increasingly allows correlations to be made between the expression of glycosyltransferases and glycan structures in cell lines, which could be extrapolated to RNAseq data from primary cells. Glycopeptide analysis will also be invaluable in providing details of specific glycan occupancy on glycoproteins, even if only as a snapshot in time. Functional studies on CD19, CD138/SDC1 and BCMA/TNFRSF17 have already demonstrated the importance of their glycosylation. Additional studies using such approaches are likely to find many more other instances in which malignant B-cell homeostasis is regulated by glycosylation, and lead to the identification of new targets to treat B-cell malignancies.